USING TOBACCO FROM CANNABIS PLANTS TO REPLACE NICOTINE-CONTAINING TOBACCO - Sinprasitkul, Wichet (Rangsit Journal of Law and Society, 2021)
It is widely recognized that the toxic effects of nicotine-containing cigarette smoking pose a danger to the health of both smokers and those who inhale cigarette smoke. cause cancer and other diseases Followed by many that are harmful to the health of the person and those around him. Affects the development of children and youth and the development of affected societies. from the aforementioned problem This research is a qualitative and field research. The objectives of the research study were: 1. To study the possibility of Using cigarette from cannabis plants to replace nicotine-containing cigarette in reducing harm 2.To study, analyze and compare the Using cannabis-derived tobacco to replace nicotine-containing cigarette in harm reduction study abroad It is hypothesized that this problem could be solved by using substitutes that have similar effects but are less harmful. Studies have shown that countries, especially in the continental regions such as Switzerland, The Federal Republic of Germany, for example, has used cannabis plants as a substitute. smoking addiction In other words, marijuana cigarettes are produced for sale. To allow consumers to replace cigarettes from cigarette with nicotine, which is harmful to health. by providing similar properties This is to reduce the dangers of using harmful substances. This is both a preventive measure and a treatment at the same time. Thailand’s drug policy should be revised and enacted legislation allowing the use of cannabis plant-based drugs to produce marijuana cigarettes so that those who are still dependent on smoking can use it instead.